Ground Reaction Force Analysis in Para-Athletes with Various Impairments: A Scoping Review - Muhammad Tasa Kasumbung; Umi Budi Rahayu; Suryo Saputra Perdana; Retno Setianing (Universitas Negeri Semarang, 2025)
Background: Para-sport provides a new meaning of life for people with disabilities giving them the opportunity to compete nationally and globally, the achievements obtained will have a positive impact on the quality of life, social and economic. To achieve all of this requires biomechanical analysis such as ground reaction force to the specific needs of para-athletes. Objective: To determine the changes in ground reaction force (GRF) in para-athletes with various impairments. Methods: Following PRISMA guidelines, studies from 2015 to 2025 were analyzed in Scopus, PubMed, Springer, and Google Scholar. The eligible study examined para-athletes with a focus on the variable ground reaction force. Results: the 87 articles obtained 8 articles met the inclusion criteria. The participants was 97 (12.88 ± 6.97). Quality assessment (6.75 ± 0.7). This review identified significant differences in GRF between para-athletes and healthy athletes, especially in those with uTFA. Asymmetry in vertical and anterior-posterior GRFs is observed between affected and unaffected limbs in athletes with uTFA. Conclusions: This review emphasizes the importance of understanding GRF patterns in para-athletes to improve training methods, prosthetic design, and injury prevention strategies. These findings highlight the need for individualized programs that consider the unique biomechanical challenges of para-athletes.